ARTE, TÉCNICA E MERCADO: ressonâncias da indústria fonográfica entre as descontinuidades da cibercultura - PAIVA, Ellen Caroline Vieira de (2012)
This paper discusses the relationship between art, technology and market from socio -cultural phenomena on the convergence between the markets and digital music. If, at first, the proliferation of music piracy in the late twentieth century raised the idea that the dynamics of metamorphoses of digital network declared bankrupt music industry consolidated in the thirties, which occurs at the end of the first decade of this century, is the implementation and optimization of a new market that combines both the traditional economic forms of the industry dictates decadent as increasing the possibilities opened up by the horizon of understanding of cyberculture. Attempts to deconstruct the discourse of decadence of the culture industry in the face of the multiplicity of the Internet featuring an underlying problem, and therefore more current, this question here vintage shifted the problem of ownership of content and marketing established between the music labels, artists and audience to the conflict between technology companies and content owners in the applications market. The convergence of media un-territorialized a univocal cultural market network and puts musicians, listeners, businesses, equipment and pirates. On this track, the network itself discusses, since the applications market presents itself as a reaction to the financial discontinuities promoted by peer-to-peer and laws, as phenomena later serve as traces of the dynamics of adaptation promoted by such constructs socio-economic and cultural. Deconstruction sometimes used as a lens designed to support the Oi Novo Som Project, the national telecommunications company Oi, who launched the independent band in the music Sobrado 112 from the network. This observation enabled us to verify, first, such as market access for new artists has been expanded from economic and technological tools, and deeper, as technology companies have diversified their marketing strategies in addition to its products and seeking to win the essential raw materials of this new market: connecting devices and storage (hardware) and content (software). While content, music becomes a commodities devices offering the means of enjoyment in the market.